The new animism and its challenges to the study of religion - Laack, Isabel (Method & theory in the study of religion, 2020)
In the last decades, the worldview(s) of so-called Indigenous religions have regained academic interest. Scholars of religion, anthropologists, and Indigenous writers engage in a new research field called new animism characterized by a diversity of insider and outsider positions. The field contains immense potential for inspiring general debates in the study of religion because it touches on fundamental questions about hermeneutics, epistemology, epistemic goals, disciplinary identities, and the influence of Western ontology on scientific and academic research.This article aims to draw the attention of scholars of religion to the new animism by contextualizing the field within disciplinary and cultural history, presenting its core theories, analyzing its methodological and epistemological positions, and identifying the central players ands its politically highly charged social contexts with asymmetrical power relations. Finally, it discusses how the new animism challenges general debates within the study of religion and may provocatively stimulate them.
Keywords: Religionsanthropologie; Animismus; Postmoderne; Religionswissenschaft